Análisis criminalístico del perfil biológico antropológico - Sánchez Hernández, Hugo (Archivos de criminología, seguridad privada y criminalística, 2020)
The criminalistic is an auxiliary discipline of criminal sciences, multidisciplinary that adopts scientific knowledge of different sciences for the examination and analysis of sensitive and significant materials related to a fact of legal significance, applying techniques and tools for the location, fixation, lifting, packaging and labelling of any indication and / or evidence. Criminalistic proposes to adopt theoretical and practical knowledge of forensic anthropology to relate to the importance of preservation and identification, to help with a more efficient and quality work when handling skeletal remains and to preserve any important biological material of a particular case. Agencies responsible for delivering justice need these forensic sciences in collaboration for specialization in handling of bones and subsequently anthropological identification through biological inferences "biological profile" to identify and clarify a fact of legal significance.